1987
DOI: 10.1002/mrm.1910040307
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular sodium and lithium NMR relaxation times in the perfused frog heart

Abstract: We have used a combination of a shift reagent and mathematical filtering or presaturation of the extracellular sodium resonance for the quantitative investigation of the intracellular sodium and lithium relaxation times in the perfused frog heart. While the T1 of the intracellular sodium was found to consist of a single-exponential time constant (approximately 23 ms), the T2 was better fit as a double-exponential decay with time constants of approximately 2 and 17 ms. However, the relative amplitudes of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 8 publications
5
48
0
Order By: Relevance
“…In living tissue, sodium exhibits at least two transverse relaxation components in both the intra-and extracellular environments. Our in vivo, volume-averaged, T 2 measurements recorded directly from normal dog hearts are in agreement with previously published values in isolated nonperfused (12) and perfused rat and frog hearts (12)(13)(14)32), as well as in dog hearts in vivo (3). The close agreement of our T 2f and T 2s values with previously published intracellular T 2f and T 2s values, obtained with administration of shift reagents (14,32), suggests that the primarily quadrupolar interactions contributing to T 2f inside the cell are comparable to those in the extracellular space.…”
Section: Biophysical Changes In Relaxation Timessupporting
confidence: 91%
See 1 more Smart Citation
“…In living tissue, sodium exhibits at least two transverse relaxation components in both the intra-and extracellular environments. Our in vivo, volume-averaged, T 2 measurements recorded directly from normal dog hearts are in agreement with previously published values in isolated nonperfused (12) and perfused rat and frog hearts (12)(13)(14)32), as well as in dog hearts in vivo (3). The close agreement of our T 2f and T 2s values with previously published intracellular T 2f and T 2s values, obtained with administration of shift reagents (14,32), suggests that the primarily quadrupolar interactions contributing to T 2f inside the cell are comparable to those in the extracellular space.…”
Section: Biophysical Changes In Relaxation Timessupporting
confidence: 91%
“…Measured T 2f , and T 2s relaxation times for total tissue sodium in the in vivo normal and infarcted animals are shown on Table 2 and compared with measurements reported in the literature over the last 15 years (12)(13)(14)(15)(16)(17) Figure 5 shows the variation of total sodium content by 23 Na MRI and AAS in control, noninfarcted, and infarcted dog hearts. Overall, sodium content values using 23 Na MRI from normal viable myocardium yielded mean estimates of 34.4 Ϯ 2.8 mmol/kg wet wt, which agreed with the mean estimate from AAS of 31.3 Ϯ 5.6 mmol/kg wet wt (P ϭ NS).…”
Section: Relaxation Measurementsmentioning
confidence: 99%
“…Goldberg et al (26) found values of 6 and 45 ms for halotolerant bacteria under high and low salt conditions, respectively. In isolated frog heart, Burstein and Fossel (27) found a T 2i of 31 ms. In the only prior in vivo result, Ramaprasad (38) found 3 ms for rat thigh muscle, if we identify his fastrelaxing component with T 2i .…”
Section: Discussionmentioning
confidence: 95%
“…A fit to a biexponential is physiologically and anatomically justified based on a simple, two-compartment, intraor extracellular model of the brain. This model has been commonly used in the past (23)(24)(25)(26)(27)(31)(32)(33)38). Importantly, the two T 2 s differ by a factor of about 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation